Case of Eosinophilic Cystitis Treated with Suplatast Tosilate as Maintenance Therapy - Tateki Yoshino; Hiroyuki Moriyama (Case Reports in Urology)
Eosinophilic cystitis is a rare inflammatory lesion of the bladder, characterized by massive eosinophilic infiltration of the bladder wall. Its cause is not known definitely. A 49-year-old man consulted our department with a miction pain, gross hematuria, and frequent micturition. Urinalysis showed combined hematuria and pyuria, but urine culture was sterile. Abnormal findings of laboratory examination included an elevated white blood cell (WBC) count (15,700/μL) and the proportion of eosinophils in the peripheral blood was 12% of the WBCs (normal 0–5%). Cystoscopy revealed a solid mass with severe edematous mucosa. Magnetic resonance imaging (MRI) also indicated marked bladder wall thickening, which was suspected for invasive bladder cancer. Transurethral biopsy of the bladder mass was performed with pathological examination revealing features of eosinophilic cystitis. After administration of a combination of prednisolone and suplatast tosilate, followed by monotherapy with suplatast tosilate, regression of the bladder mass, and normalization of the count of peripheral eosinophils were achieved. Fourteen months after steroid therapy, under treatment with suplatast tosilate, there was no relapse of urinary symptoms and the bladder mass.